ANALISIS KEMAMPUAN EKSPOR KOMODITAS PERTANIAN DI KECAMATAN DELANGGU KABUPATEN KLATEN DENGAN PENDEKATAN ANALISIS LOCATION QUOTIENT - Nuning Setyowati; Mei Tri Sundari (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2005)
This research aim to identify sector becoming base in Delanggu sub district, agriculture commodity becoming base in Delanggu sub district and to know the export capacity of agriculture commodity. Used method is descriptive method with Location Quotient (LQ) analysis mean